Irrigation system modernization in the Middle Rio Grande Valley - Gensler, David, author; Oad, Ramchand, author; Kinzli, Kristoph-Dietrich, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
The Middle Rio Grande Conservancy District (MRGCD) was officially founded in the 1920's, but it may well be the oldest operating irrigation system in North America. Prior to the arrival of European explorers, the area's Pueblo cultures were practicing flood irrigation along the banks of the Rio Grande. More elaborate irrigation practices were introduced to the Middle Rio Grande Valley by Spanish explorers in the 1600's and irrigation and water delivery practices have remained virtually unchanged for the past 300 to 400 years. Currently the MRGCD serves about 55,000 acres of irrigated land and provides additional benefits to the Middle Rio Grande (MRG) Valley by providing water for domestic, industrial, and environmental needs. In recent years the demand for water in the Middle Rio Grande Valley has increased drastically due to explosive population growth, expanding industry, and water allocated for environmental and ecological concerns, that include two federally listed endangered species -- the silvery minnow (Hybognathus amarus), and the southwestern willow fly catcher (Empidonax traillii extimus). In response to the call for more efficient water use, the MRGCD embarked on a program of irrigation system modernization with SCADA incorporation. Over the past few years, the MRGCD has developed a SCADA system with the focus being to improve water use efficiency throughout the Middle Rio Grande Valley. This paper examines the five components of the system and how each component was developed and incorporated in the overall SCADA system. The SCADA system and related improvements in operational practices have reduced MRGCD river diversions from 600,000 AF/year to an average of 350,000 AF/year over the last three years.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.